THE IMPACT OF EMPLOYER BRANDING ON JOB SEEKER ATTRACTION: THE MEDIATING ROLE OF PERCEIVED EMPLOYER ATTRACTIVENESS AND THE MODERATING EFFECT OF COMPETITOR INFLUENCE - A CASE STUDY OF VJC - Tanni Tanni; Neneng Nurlaela Arief (Politeknik Negeri Ambon, 2026)
Introduction: This research examines the influence of employer branding on job-seeker attraction in the luxury fashion e-commerce industry, using VJC as a case study. Amidst fierce competition in the labor market, especially for digital and creative roles, employer branding is a key strategy to attract top talent. However, challenges arise when companies like VJC have to compete with widely recognized global brands. This study aims to determine whether employer branding is sufficient to drive application intentions, whether its effectiveness depends on perceptions of the company’s attractiveness as a workplace, and whether the presence of competitors affects the relationship. Method: This study uses a quantitative approach employing Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were obtained from 166 respondents interested in digital technology and products. The three main constructs analyzed were employer branding, perceived employer attractiveness, and job seeker applications, with competitor influence as a moderating variable. Result: Results show that employer branding has no direct effect on application intentions, but significantly affects perceived employer attractiveness, which in turn leads to increased application intentions. Competitor influence is shown to moderate this relationship; when competitor branding is stronger, the effect of perceived attractiveness on application intentions is weakened. These findings confirm that employer branding occurs in a competitive context, where perceptions of competitors largely determine the effectiveness of a company's branding strategy. Keywords: Competitor Influence, Digital Talent, Employer Attractiveness, Employer Branding, Job Seeker Application, Luxury Fashion, Perceived